PRICE DISCRIMINATION, ENTRY, AND SWITCHING COSTS IN NETWORK COMPETITION - Trifunović, Dejan; Mitrović, Đorđe (Economic Annals, 2016)
This paper reviews theoretical models of network competition in telecommunications. We will discuss two alternative approaches. The first approach assumes Hoteling’s horizontal differentiation and the second approach is based on switching costs. We will first analyse spatial competition with linear prices and continue with price discrimination between onnet and off-net calls. Price discrimination can also be used to deter entry to the market. We will also deal with the regulator’s optimal choice of access price, which should be designed to induce entry of new firms. Furthermore, pricing of roaming services and the switching cost approach to network competition will be considered. Finally, we will illustrate the theoretical results with data from the Serbian mobile and fixed telephony market.